Ginsenoside Rg1 activates ligand-independent estrogenic effects via rapid estrogen receptor signaling pathway - Gao, Quan-Gui (J Ginseng Res, 2019)
BACKGROUND: Ginsenoside Rg1 was shown to exert ligand-independent activation of estrogen receptor (ER) via mitogen-activated protein kinase–mediated pathway. Our study aimed to delineate the mechanisms by which Rg1 activates the rapid ER signaling pathways. METHODS: ER-positive human breast cancer MCF-7 cells and ER-negative human embryonic kidney HEK293 cells were treated with Rg1 (10(−12)M, 10(−8)M), 17ß-estradiol (10(−8)M), or vehicle. Immunoprecipitation was conducted to investigate the interactions between signaling protein and ER in MCF-7 cells. To determine the roles of these signaling proteins in the actions of Rg1, small interfering RNA or their inhibitors were applied. RESULTS: Rg1 rapidly induced ERα translocation to plasma membrane via caveolin-1 and the formation of signaling complex involving linker protein (Shc), insulin-like growth factor-I receptor, modulator of nongenomic activity of ER (MNAR), ERα, and cellular nonreceptor tyrosine kinase (c-Src) in MCF-7 cells. The induction of extracellular signal-regulated protein kinase and mitogen-activated protein kinase kinase (MEK) phosphorylation in MCF-7 cells by Rg1 was suppressed by cotreatment with small interfering RNA against these signaling proteins. The stimulatory effects of Rg1 on MEK phosphorylation in these cells were suppressed by both PP2 (Src kinase inhibitor) and AG1478 [epidermal growth factor receptor (EGFR) inhibitor]. In addition, Rg1-induced estrogenic activities, EGFR and MEK phosphorylation in MCF-7 cells were abolished by cotreatment with G15 (G protein-coupled estrogen receptor-1 antagonist). The increase in intracellular cyclic AMP accumulation, but not Ca mobilization, in MCF-7 cells by Rg1 could be abolished by G15. CONCLUSION: Ginsenoside Rg1 exerted estrogenic actions by rapidly inducing the formation of ER containing signalosome in MCF-7 cells. Additionally, Rg1 could activate EGFR and c-Src ER-independently and exert estrogenic effects via rapid activation of membrane-associated ER and G protein-coupled estrogen receptor.